Understanding the changes in Sri Lankan mango fruits during postharvest ripening - Thanaraj, Thiruchelvam (Cranfield University, 2010)
This is the first study to be carried out which describes changes in biochemical profile of both pre- and post-climacteric Sri Lankan mango fruits. Chemometric analysis revealed that spatial distribution of biochemical compounds between peel and pulp was the major discriminatory factor during maturation; whereas fully mature mango fruit contained the highest concentration of starch and lowest concentration of acids. Since these combined variables also responsible for the final quality of ripe fruit, they could be used as important parameters of horticultural maturity to inform growers to harvest Sri Lankan mango fruit at the optimum stage. Cont/d.